Education, Migration and Development Critical Perspectives in a Moving World - North, Amy; Chase, Elaine (Bloomsbury Academic, 2022)
This open access book critically explores how education, migration and development intersect and interact to shape people, communities, societies, ideas, values, and action at local, national and international levels. Written by leading scholars and practitioners from across the globe, the book introduces the reader to how such interactions play out through a series of illustrative case studies drawn from scholarship and empirical research conducted in the global South. It considers education in all its forms and raises critical questions about its purpose and value in contexts of migration and (im)mobility across a range of low- and middle-income settings. The contributors engage with the multiple reasons for migration, and also consider how communities and societies are shaped not just by the movement of people but also of ideas, resources, norms, and values across different national and international contexts. Collectively the chapters offer new insights into: the considerations for education and international development that emerge when we apply a migration lens; key theoretical frameworks and approaches which can help us understand the education-migration-nexus; the opportunities and challenges that migration and (im)mobility create for education in contexts of development; emerging dilemmas regarding how best to promote justice, equity and wellbeing in and through education in contexts of migration; and how gendered and other inequalities are core considerations in the education-migration-development nexus. The book concludes with some reflections by the editors on cross-cutting themes generated through the volume, including some directions for future research. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollection.com. Open access was funded by Knowledge Unlatched.